CUM SĂ GĂSEŞTI O CARTE DE… MUNCĂ? - COSTIUC, Tatiana (BIBLIOPOLIS, 2020)
The article is about the project „How to find a job” initiated by Ana Maria Dudescu, chief of Kids Departement of the County Library „Octavian Goga” Cluj, România. The project was developed in the Community participation contest launched by national program Biblionet. The final aim of the project was the creation of innovative service in library – the counseling in an employment contest, including: writing a resume, preparing a letter of intent, passing a job interview and job search via the Internet.